2022
DOI: 10.1055/a-1834-9008
|View full text |Cite
|
Sign up to set email alerts
|

Liver, NAFLD and COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is characterized by a wide clinical spectrum that includes abnormalities in liver function indicative of liver damage. Conversely, people with liver diseases are at higher risk of severe COVID-19. In the current review, we summarize first the epidemiologic evidence describing the bidirectional relationship between COVID-19 and liver function/liver diseases. Additionally, we present the most frequent histologic findings as well as the most important direct and indirect mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…Furthermore, other mechanisms such as an increased susceptibility to infections, a reduced immune Response, and an increased risk of coagulation could contribute to a higher risk of severe COVID-19 in people with NAFLD [106].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other mechanisms such as an increased susceptibility to infections, a reduced immune Response, and an increased risk of coagulation could contribute to a higher risk of severe COVID-19 in people with NAFLD [106].…”
Section: Discussionmentioning
confidence: 99%
“…"Cytokine storm" was often observed in severe COVID-19 and could lead to multiple organ failures, including severe liver damage [34,35]. A recent study demonstrated that IL-6 was probably the main cytokine orchestrating this inflammatory response leading to liver damage [36]. Given that systemic inflammatory response syndrome (SIRS) induces inflammation in multiple tissues, including the liver, it is reasonable to assume that it may further aggravate a pre-existing inflammatory state, like the one observed in NASH [37].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Notably, individuals suffering from NAFLD are at higher risk of developing coronavirus disease 2019 (COVID-19). [5,6] Meanwhile, the enhanced physical inactivity, overeating and depression associated with COVID-19 exert adverse effects on NAFLD, ultimately contributing to elevated liver-related mortality. [7] In recent years, increasing efforts have been given towards management of fatty liver diseases using nutraceuticals, over the last decade with obvious increase in research papers from 16 records in 2008 to reach 218 in 2022 as retrieved by searching SCOPUS database for literature using keywords of cereal polyphenols (Appendix A1, Supporting Information, and Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Notably, individuals suffering from NAFLD are at higher risk of developing coronavirus disease 2019 (COVID‐19). [ 5,6 ] Meanwhile, the enhanced physical inactivity, overeating and depression associated with COVID‐19 exert adverse effects on NAFLD, ultimately contributing to elevated liver‐related mortality. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%